2013
DOI: 10.1111/zsc.12012
|View full text |Cite
|
Sign up to set email alerts
|

The systematic position of Ergasticus (Decapoda, Brachyura) and allied genera, a molecular and morphological approach

Abstract: The complete larval series (zoea I, zoea II and megalopa) of the crab Ergasticus clouei is described and illustrated based on plankton samples from Mediterranean waters. The zoea II and megalopal stages, previously unknown, are described here for the first time. Nucleotide sequence analysis of two gene regions (16S rDNA and Cox1 genes) confirmed the assignment of these larvae to Ergasticus clouei. The molecular analyses and the morphology of the larval stages revealed large differences between Ergasticus and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
0
20
0
1
Order By: Relevance
“…A recent study based on larval morphology and DNA did not support a clear separation between epialtid and pisid crabs (Hultgren and Stachowitz 2008). Neverthe- (Marco-Herrero et al 2013a). Within the Grapsoidea superfamily, the former Grapsidae is now restricted to the previous subfamily Grapsinae, while other subfamilies that acquired familial level (e.g.…”
Section: Systematic Remarksmentioning
confidence: 99%
“…A recent study based on larval morphology and DNA did not support a clear separation between epialtid and pisid crabs (Hultgren and Stachowitz 2008). Neverthe- (Marco-Herrero et al 2013a). Within the Grapsoidea superfamily, the former Grapsidae is now restricted to the previous subfamily Grapsinae, while other subfamilies that acquired familial level (e.g.…”
Section: Systematic Remarksmentioning
confidence: 99%
“…Marco-Herrero et al (2013) for Majoidea; Schubart and Reuschel (2009) and Spiridonov et al (2014) for Cancroidea and Portunoidea). Superfamilies are listed by systematic order following the Sections and Subsections as currently accepted, and by alphabetical order within them.…”
Section: Methodsmentioning
confidence: 99%
“…Morphology of Polycheles typhlops larvae Accurate identification of marine larvae has traditionally required the rearing of larval stages in aquaria, but the development of species-specific markers (DNA barcoding) facilitates now the assignment of wild-caught planktonic larvae (Palero et al 2008;Marco-Herrero et al 2013). Matzen da Silva et al (2011) have recently shown that the standard DNA barcoding COI gene region resolves relationships among decapod crustaceans.…”
Section: Discussionmentioning
confidence: 99%